Concordance between self-reported SARS-CoV-2 positivity and laboratory-confirmed positivity - Catalfamo, Collin James; Jacobs, Elizabeth T.; Falk, Laura P.; Lauro, Priscilla; Ernst, Kacey C.; Farland, Leslie V.; Heslin, Kelly M.; Pogreba-Brown, Kristen; Garcia-Filion, Pamela C. (PloS one, 2025)
As the use and availability of at-home antigen tests for SARS-CoV-2 infection have increased, the number of individuals with SARS-CoV-2 infections that are reported to state COVID-19 surveillance systems have decreased. Self-reported infection dates are critical to accurately track incidence and outbreaks of COVID-19 and for continued research on illness progression; however, the reliability of self-reported infection dates is unknown to date. To assess accuracy of self-reported test dates, we utilized self-reported SARS-CoV-2 testing data from the Arizona CoVHORT Study (CoVHORT) and laboratory-confirmed testing data collected by the Arizona Department of Health Services (ADHS) and calculated the difference in days between dates to examine their percent agreement. We used logistic regression to assess if any participant characteristics were associated with self-reporting a test date >7 days different than the laboratory confirmed date. A total of 1,900 CoVHORT participants aged 18 years or older were included in our analyses. Most participants (82.5%) reported a test date within 7 days of the laboratory confirmed date of their illness. Increasing age and number of weeks between testing positive and self-reporting the test date were both significantly associated with a difference of 7 days or greater between dates. There was an 84% increase (OR=1.84, 95% CI = 1.11–3.06) in likelihood of inaccurately self-reporting their SARS-CoV-2 test date for participants aged 55 years and older and a 2% increase (OR=1.02, 95% CI = 1.02–1.03) for each elapsed week following their SARS-CoV-2 test. We observed an 82% percent agreement (dates within 7 days of each other) between self-reported and laboratory confirmed test dates, suggesting that self-reported SARS-CoV-2 test dates are sufficient for identifying and tracking Long COVID or Post-COVID Conditions when a laboratory-confirmed test date is not available. However, increasing age and greater time between test date and date of self-report were found to decrease the agreement between self-reported and laboratory confirmed test dates.